2004
DOI: 10.1161/01.str.0000143455.55877.b9
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted MRI in 300 Patients Presenting Late With Subacute Transient Ischemic Attack or Minor Stroke

Abstract: Background and Purpose-Many patients with transient ischemic attack (TIA) or minor stroke present to medical attention after a delay of several days or weeks, at which time it may be more difficult to obtain a clear history and clinical signs may have resolved. Because ischemic lesions on diffusion-weighted MRI (DWI) often persist for several weeks, we hypothesized that adding DWI to a standard protocol with T2-weighted imaging might be useful in the management of patients presenting late. Methods-We studied c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 30 publications
6
50
2
Order By: Relevance
“…6 The audit also demonstrates imaging is more likely to be diagnostic when performed early. 7,8 This supports the National Stroke Strategy recommendation for immediate referral in patients presenting with a recent TIA or minor stroke. 10 Although not a subject of this audit, interventions to prevent stroke have also been shown to be time dependent, 2 again reinforcing the need for urgent evaluation and management of patients with minor stroke or TIA.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…6 The audit also demonstrates imaging is more likely to be diagnostic when performed early. 7,8 This supports the National Stroke Strategy recommendation for immediate referral in patients presenting with a recent TIA or minor stroke. 10 Although not a subject of this audit, interventions to prevent stroke have also been shown to be time dependent, 2 again reinforcing the need for urgent evaluation and management of patients with minor stroke or TIA.…”
Section: Discussionsupporting
confidence: 52%
“…For this clinic, magnetic resonance imaging (MRI), including diffusion weighted imaging, was the primary brain imaging modality and carotid magnetic resonance angiogram (MRA) was the primary vascular imaging used, and they were generally performed together. 7,8 Stroke and TIA were diagnosed according to World Health Organization (WHO) criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Four studies provided data separately for TIA and minor stroke patients. 224,225,232,233 The proportion of minor stroke patients with visible ischaemic lesions on DWI was 47% in one study, 227 70% in another study, 232 and reached 100% in two studies. 224,233 It is worth noting that the two studies in which all minor stroke patients showed a positive DWI lesion were of small sample size and enrolled patients with a definite diagnosis of TIA or minor stroke as opposed to a possible diagnosis of TIA or minor stroke -for example Kastrup and colleagues 224 included only patients with high-grade symptomatic carotid stenosis.…”
Section: Main Findingsmentioning
confidence: 93%
“…All studies except eight 57,72,134,224,225,232,233,248 restricted inclusion to TIA patients. The frequency of positive DWI findings ranged from 9% to 67% across studies (Table 22).…”
Section: Main Findingsmentioning
confidence: 99%
“…15,16 This is of particular concern in clinical settings where urgent neurology follow-up or access to primary care is not available. Furthermore, multiple studies have documented that patients with TIA who have evidence of infarct on magnetic resonance imaging (MRI) are at substantially increased risk of stroke, [17][18][19][20][21][22] and incorporation of MRI findings into the risk stratification process substantially improves prognostication. 23 As a result, national guidelines now recommend MRI as the ''preferred'' brain imaging modality over noncontrast computed tomography (CT).…”
Section: Introductionmentioning
confidence: 99%